Laparoscopic Treatment of Intestinal Malrotation in Children - Ooms, Nina; Matthyssens, Lucas E. M.; Draaisma, Jos MTh; de Blaauw, Ivo; Wijnen, Marc H. W. A. (European Journal of Pediatric Surgery, 2016)
Purpose Intestinal malrotation is a congenital intestinal rotation anomaly, which can be treated by either laparotomy or laparoscopy. Our hypothesis is that laparoscopic treatment leads to less small bowel obstruction because of the fewer adhesions in comparison to laparotomy, without increasing the risk of recurrent volvulus. We analyzed the outcome of patients who had a correction for intestinal malrotation after the introduction of laparoscopy.Methods All patients between 0 and 18 years who underwent a surgical procedure for malrotation in the Radboudumc Amalia Children's Hospital, Nijmegen, the Netherlands, between January 2004 and December 2011 were retrospectively reviewed for duration of operation, perioperative complications, length of hospital stay, and rate of redo surgery for intestinal volvulus or obstruction.Results A total of 83 patients were included of which 33 had a laparoscopic procedure and 50 had a laparotomy for suspected malrotation. Operating time was 63 minutes for the laparoscopic procedure versus 76 minutes for laparotomy (p = 0.588). Significantly more complications were found in the laparotomy group (11 vs. 35%, p = 0.047). However, one patient (aged 4 months) in the laparoscopy group developed an early (< 24 hours) recurrent volvulus. Length of hospital stay was significantly longer after a laparotomy (9 vs. 16 days, p = 0.002). Three (17%) patients in the laparoscopy group needed redo surgery compared with six (9%) in the laparotomy group (p = 0.400). No late volvulus occurred in both groups. After laparotomy, redo surgery because of the small bowel obstruction was more frequent (5 vs. 0%), although this was not statistically significant.Conclusion In both the laparoscopy and laparotomy group, no cases of long-term recurrent volvulus were seen. After laparotomy, more patients developed a late small bowel obstruction because of the adhesions for which redo surgery was needed. In the laparotomy group, the number of complications was significantly higher and the length of hospital stay was significantly longer. Comparing laparoscopy and laparotomy for the treatment of malrotation, no difference exists for the long-term risk of recurrent volvulus. In children aged 6 months or older with suspicion of intestinal malrotation but not presenting with an acute abdomen or hemodynamically instability, laparoscopy should be considered as a first approach to diagnose and subsequently treat intestinal malrotation.
Keywords: malrotation; laparoscopy; Ladd procedure; redo surgery; volvulus